Penguatan Tata Kelola Koperasi Berbasis Digital di Desa Wisata Candirejo Magelang: Upaya Meningkatkan Efisiensi dan Akuntabilitas - Anis Susanti; Ismiyati Ismiyati; Sandy Arief; Risanda Alirastra Budiantoro; Mulil Khaira (Universitas Negeri Gorontalo, 2025)
This community service program aims to strengthen the governance of the Candirejo Tourism Village Cooperative in Magelang through the digitalization of archiving and financial recording systems. The main issue addressed is the limited use of information technology, as administrative and financial records are still managed manually, resulting in inefficiency and low accountability. A participatory approach was applied, including digital archive management training and the development of a web-based information system. The training involved 30 participants and was followed by intensive assistance for system implementation. The results show that 87% of participants demonstrated improved competence in using the system, 92% of physical archives were digitized, and 94% of financial transactions were accurately recorded in the new system. Moreover, 85% of sales reports can now be accessed in real time by cooperative managers. These measurable outcomes indicate that combining participatory training with context-appropriate technology significantly enhances efficiency, accuracy, and transparency in cooperative management. The program is expected to be expanded through follow-up training, policy support at the village level, and collaboration with technology providers to sustain and further develop the system.